Scabronine G Methyl Ester Improves Memory-Related Behavior and Enhances Hippocampal Cell Proliferation and Long-Term Potentiation via the BDNF-CREB Pathway in Olfactory Bulbectomized Mice - Nakagawasai, Osamu; Lin, Jia-Rong; Odaira, Takayo; Takahashi, Kohei; Nemoto, Wataru; Moriguchi, Shigeki; Yabuki, Yasushi; Kobayakawa, Yu; Fukunaga, Kohji; Nakada, Masahisa; Tan-No, Koichi (Frontiers in Pharmacology, 2020)
A previous study reported that scabronine G methyl ester (SG-ME) potentially enhances the in vitro secretion of neurotrophic factors such as nerve growth factor (NGF) via the protein kinase C (PKC)-ζ pathway. However, it remains unknown whether SG-ME can improve cognitive dysfunctions in olfactory bulbectomized (OBX) mice. To address this question, we evaluated SG-ME-treated and untreated OBX mice in a passive avoidance test. We also investigated potential effects of SG-ME on several parameters: cell proliferation and cAMP response element-binding protein (CREB) phosphorylation in the hippocampal dentate gyrus by immunohistochemistry, brain-derived neurotrophic factor (BDNF) levels in the hippocampus by Western blotting, p-CREB levels in the hippocampus by MapAnalyzer, and long-term potentiation (LTP) by electrophysiology. On the 14th day after surgery OBX mice showed altered passive avoidance and decreases in both cell proliferation and LTP in the hippocampus, while these changes were reversed by SG-ME (20 μg/mouse) 24 h after the treatment. The improvement in memory deficits was prevented when SG-ME was co-administeredwith either ZIP (PKC-ζ inhibitor), anti-BDNF antibody, ANA-12 (TrkB antagonist), U0126 (MEK inhibitor), H-89 (PKA inhibitor), LY294002 (PI3K inhibitor) or KN-93 (CaMKII inhibitor). We found that SG-ME enhanced BDNF and p-CREB levels in the hippocampus while p-CREB was localized in neurons, but not in astrocytes nor microglial cells. These findings revealed the potential of SG-ME in improving memory impairments by enhancing cell proliferation and LTP via activation of the BDNF/CREB signaling pathway in neurons.